Las estrategias de andamiaje en el desarrollo de las habilidades de escritura entre los estudiantes de octavo año de educación básica fiscomisional san juan bautista de la Salle sección vespertina de la cuidad de Loja durante el año escolar 2018-2019 - Castillo Zhamungui, Jhoselyn Ximena (2019)
The objective of the following research work was to develop writing skills through scaffolding strategies among students of eighth year at Escuela de Educación Básica Fiscomisional San Juan Bautista de la Salle afternoon session of Loja city during the 2018-2019 school year. The methods applied were: analytical-synthetic, statistical, scientific and descriptive, which allowed the researcher to describe, interpret, analyze and discuss the obtained data. Two tests and questionnaires were applied to twenty-three students to diagnose and compare their knowledge and attitudes. Observation sheets and field notes were used by the researcher to record participants behavior. The results showed that the students improved their writing skills from a failing level to an average level, they presented a better understanding about the writing process in the use of vocabulary, punctuation, grammar, sentence structure and organization of ideas. In conclusion, the scaffolding strategies were effective and increased the motivation in the students to write and participate actively in developing writing activities.